Baptism of desire and Christian salvation - Lusvardi, Anthony (Washington,D.C. The Catholic University of American Press, 2024)
"Arguing that theologians of the past two centuries have tended to downplay the role of the sacraments when discussing salvation, Lusvardi suggests that baptism should remain our theological starting point. Engaging with the theological tradition and at times challenging the conventional wisdom, Baptism of Desire and Christian Salvation shows how such a sacramental approach can offer credible-and sometimes surprising-responses to questions related to the salvation of non-Christians, the fate of unbaptized infants, and the relevance of the Church's mission today"--
Includes bibliographical references (pages 363-388) and index.
Keywords: Baptism -- Catholic Church; Salvation